Challenges in Re-Entry among Former Inmates : A Review - Tharshini, A/P Sivabalan; Fauziah, Ibrahim; Mohd Suhaimi, Mohamad; Ezarina, Zakaria (Human Resource Management Academic Research Society, 2018)
Failure of re-entry has been associated with risks of higher recidivism rates and is a potential factor of decreased in inmate’s well-being. This article will examine the challenges endured by the former inmates during the process of re-entry. A literature search has been performed using various keywords like “challenges”, “re-entry”, “crime”, “inmates” and “former inmates” in databases, such as Emerald, Elsevier, Sage, and Google Scholar. The results indicate that majority of the inmates undergo common challenges, which includes limited employment prospects, lack of family support, difficulties in securing housing, unstable physical/mental condition and drug dependency. Therefore, this article review is hoped to call for efforts to be made by the government and interested parties to reduce these challenges encountered by former inmates upon their prison release.